The spatiotemporal distribution and prognostic factors of Japanese encephalitis in Shanxi Province, China, 2005–2022 - Zheng, Peiyu; Wen, Zhiying; Liu, Yuan; Wang, Qinying (Frontiers in Cellular and Infection Microbiology, 2023)
Japanese encephalitis (JE) is a naturally occurring localized disease caused by the Japanese encephalitis virus, which is spread by the Culex tritaeniorhynchus. China has a high rate of JE. Shanxi, located in North China, has a high prevalence of adult JE. Adult JE has more severe complications, mortality, and a higher disease burden, making it a public health issue. This retrospective study examined the dynamic epidemic changes, high-risk areas of JE, and clinical characteristics and prognostic factors of adult JE in Shanxi Province. The findings revealed that July to September was the primary epidemic season of JE and that JE cases were mainly in individuals over the age of 40. The incidence of JE from 2005 to 2022 demonstrated a positive spatial correlation with significant clustering characteristics, with high-incidence clusters in the south and southeast. Multivariate logistic regression analysis revealed that higher cerebrospinal fluid pressure, higher white blood cell counts, higher neutrophil percentage, deep coma, and lower albumin were independent factors for poor prognosis of adult JE. The developed risk prediction model holds great promise in early prognosis assessment of patients, providing a basis for clinical decision-making and early clinical intervention. 1 2 MethodsShanxi Province is located in the east wing of the Loess Plateau in western North China, between 34°34' to 40°44' north latitude and 110°14' to 114°33' east longitude. It is a parallelogram oblique from northeast to southwest, having a total area of 156,700 square kilometers. The precipitation from June to August accounts for nearly 60% of the annual precipitation. It has jurisdiction over 117 counties or districts of 11 prefecture-level cities.